Peramalan Jumlah Kunjungan Wisatawan Mancanegara (Wisman) Ke Bali Tahun 2019: Metode ARIMA - Rukini, Rukini; Simpen Arini, Putu; Nawangsih, Esthisatari (Jurnal Ekonomi Kuantitatif Terapan; 2015: Vol. 8, No. 2, Agustus 2015 (pp. 113-216), 2015)
IndonesiaTourism has been growing significantly over the past few years. In 2013, income from tourism reached 10,054 millions dollars, occupied the third place of indonesia export commodities. The ministry of tourism and creatice economy has targeted 20 millions arrivals and 240 trillion rupiahs from international tourist arrivals in 2019. As Bali has been contributing for more than 40 percent of international tourist arrivals in Indonenesia, it is expected to have around 8 millions international arrivals in 2019. Using ARIMA method, it is predicted that the number of international tourist arrivals in Bali will be 5,07 millions in 2019, far below the target. This result suggests that government should give more effort to develop tourism in the upcoming years to fulfil the target.
Keywords: Target tourists; ARIMA; forecasting